Effect of plant growth regulators on leaf area, chlorophyll content, carotenoids, stomatal count and yield of cashew (Anacardium occidentale L.) var. Bhaskara - D. Kalaivanan; G.K. Halesh, Lakshmipathi, J. D. Adiga (Journal of Plantation Crops, 2017)
An experiment was conducted to study the effect of exogenous application of growth regulators at three important growth stages (flushing, flowering and fruiting) on leaf area, chlorophyll content, carotenoids, stomatal count and yield of cashew var. Bhaskara. Irrespective of growth stages, foliar application of GA3 @ 50 ppm and ethrel @ 50 ppm was found to be superior in all the parameters and on par with each other compared to other growth regulators. Out of nine treatments of different growth regulators; the highest leaf area was recorded in trees sprayed with GA3 @ 50 ppm and ethrel @ 50 ppm. At flushing stage, spraying with GA3 @ 50 ppm resulted in highest stomatal number (21.9) and carotenoids (0.41) whereas unsprayed (control) trees recorded least stomatal number (11.6) and carotenoids (0.19). Thus, leaf area, chlorophyll content, carotenoids and stomatal count increased in trees sprayed with growth regulators than unsprayed trees. Spraying of ethrel @ 50 ppm recorded highest nut yield (14.3 kg tree-1) followed by NAA @ 25 ppm + GA3 50 ppm (12.9 kg tree-1). This study demonstrated the potential of ethrel as well as GA3 in improving various biochemical parameters viz., chlorophyll ‘a’, chlorophyll ‘b’, carotenoids and leaf area in cashew which are important determinants in increasing nut production.